Author Correction: Earth's early O2 cycle suppressed by primitive continents. Issue 3 (March 2018) - Smit, Matthijs; Mezger, Klaus
In the Supplementary Information file originally published, notes were mistakenly omitted from Supplementary Table 4. This has now been corrected.